Choosing the right home: settlement responses by larvae of six sea urchin species align with hydrodynamic traits of their contrasting adult habitats. Issue 2 (23rd January 2020) - Hodin, Jason; Ferner, Matthew C; Gaylord, Brian
Abstract: Ocean organisms as diverse as seaweeds and sea cucumbers exhibit life cycles in which dispersal occurs primarily via microscopic larvae or spores, with adults exhibiting limited or even no dispersal. In benthic animals, the larval stage concludes with irreversible settlement into the benthos. The decision of where and when to settle is thus one of substantial import. Prior work has shown that settlement in two shoreline echinoids (a sea urchin and a sand dollar) is unexpectedly sensitive to an environmental feature (intense fluid turbulence) that can be considered as a signal to larvae of their arrival in the neighbourhood of the hydrodynamically energetic habitats in which these taxa live as adults. Here, we used a comparative approach to explore the evolution of turbulence responsiveness in late-stage echinoid larvae. We examined three pairs of closely related sea urchins that differ in the energetic exposure of their adult habitats and found that larval responsiveness to turbulence was more pronounced in urchins that settle in more hydrodynamically exposed locations. These results raise the possibility that evolutionary differences in larval responsiveness to environmental indicators of appropriate adult habitat might reinforce or even provide a mechanism for vicariance in the ocean.